Clinicopathologic and Immunohistochemical Characterization of Dedifferentiated Endometrioid Adenocarcinoma. Issue 8 (September 2016) - Li, Zaibo; Zhao, Chengquan
Abstract : Dedifferentiated endometrioid adenocarcinoma (DEAC) of the uterus or ovary is characterized by the coexistence of low-grade endometrioid adenocarcinoma and an undifferentiated carcinoma (UC) with solid sheets of medium-sized monotonous epithelial cells. This admixed carcinoma has not been widely recognized, because the solid areas of UC have usually been misdiagnosed as a solid form of FIGO grade 3 endometrioid adenocarcinoma. These tumors have been shown to be clinically aggressive; therefore, accurate diagnosis is necessary for proper patient management. We reviewed our experience with DEACs and compared them with grade 3 endometrioid carcinomas regarding their clinicopathologic, morphologic, and immunohistochemical features. Our results indicate that DEACs are clinically aggressive tumors presented at advanced stages with vascular invasions in 73% and lymph node metastases in 46%. Thirty-eight percent of cases also showed distal metastases. Clinical follow-up data revealed that all patients had either recurrent or metastatic diseases within 3 years of diagnosis, except 1 patient who remained disease free for 3 years after diagnosis. Morphologically, UC components of DEACs were composed of diffuse sheets/solid nests of medium-sized epithelial cells with scant to moderate cytoplasm, uniform vesicular nuclei, and inconspicuous nucleoli. Although UC components of DEACs are variably positive for cytokeratin, EMA, and ER, they are mostly negative for PAX8, except 1 case. Instead, well-differentiated components of DEACs and solid grade 3 endometrioid carcinoma retained all these markers. Our results indicate that DEACs exhibit significantly different clinicopathologic features from grade 3 endometrioid adenocarcinoma, and a combination of immunohistochemical stains can be helpful to differentiate them from each other.